To understanding of the term «language game» (Eurasian Journal of Philology Science and Education, 2016)
The article is devoted to the history of occurrence and comprehension of the terminological phrase «language game». Analyzing the writings of J. Heizing, Ludwig Wittgenstein and the work s of linguists, the author shows the evolution of the concept of «language game» in science. Rebounding from a philosophical understanding of the «language games» in the spirit of Wittgenstein, the author comes to its system-language comprehension. Examples of «language game» in the modern media of Kazakhstan served as illustrative material, particularly, in the newspapers «Vremya» and «Caravan».
Keywords: anguage game; the metaphor; verbal behavior; game transformation; the ambiguity of the word.